UPAYA MENINGKATKAN KETERAMPILAN MEMBACA DENGAN MEDIA AUDIO VISUAL PADA SISWA KELAS V SD NEGERI 13 PESING - PUJI RAHMAWATI; Siti Fitriyah Mutmainah (STKIP Melawi, 2023)
This research was motivated by the low reading skills in class V of SD Negeri 13 Pesing, Sekayam District, Sanggau Regency. The formulation of the problem is â€œWhat the use of audio-visual media improved students' reading skills at SDN 13 Pesing?â€. The purpose of this research is to improve reading skills by using audio-visual media. The type of research is Classroom Action Research (CAR). The location is in class V SD Negeri 13 Pesing. The subjects were 36 students of class V. Data collection techniques used test techniques and non-test techniques. The research instrument is a test and non-test. The results of the research on reading skills using audio-visual media have increased. Cycle I is students' reading skills completed 27 students (75%) and 9 students (25%) did not complete. As for the results of observations of student activity with a rating of 27 students (75%) in Good (B) category, 6 students (16.67%) in Enough (C) category, and 3 students (13.63%), in Poor (D) category. In cycle II, 32 students (88.87%) completed their reading skills and 4 students (11.11%) did not complete them. Student activity with a rating of Very Good (A) 32 students (88.87%), Good (B) 2 students (2.78%) and 2 students (2.78%) Fair (C).